Hernias of the esophageal hiatus of the diaphragm: tactical, surgical therapy - Suiffet, Walter; Ituño, Carlos; Estapé, Gonzalo (Cirugía del Uruguay, 1972)
Surgery requírements ín the treatment of herníatíon el t,he esophageal foramen ís analyzed; the importance of preventíng regurgitation backflow is pointed out. The approach may be either abdominal or thoracic and each case should be. analyzed accordíng to its pathology. The Puthor states hís preference for the abdominal approach, employed in the last 37 operatíons, while ín earlier cases he had employed the thoracíc approach. The latter í .s reserved for cases involvíng seríous esophagítís or high acídíty values. The abdominal approach was used 45 times ( 70 o/r¡ ) and the thoracíc 20 ( 30 % ) . Dífferent techníques are employed accordíng tho the círcumstances of ,;ach case. Favourable results have been obtaíned ín confrolled cases, whích range between 80 and 100 % . Results wíth dífferent procedures are símílar, but íj: ís belíeved thís ís due to theír díscrímínate application in each sítuation. Favourable results amount to 85 % of controlled cases and 72 % of all patíents operated ín thís series. Morbílíty rate was 37 .5 % and death rate 1.5 % .